Elaboración de un manual de buenas prácticas de manufactura (bpm), en la empresa de lácteos verito en la parroquia de Alóag, barrio Aychapicho 2012 - Pilaguano Caiza, Patricio Javier (2015)
Good Manufacturing Practices are principles that apply to all processes handling of processed foods and are a key means of developing healthy and safe food for the consumer tool. This study was conducted with the aim of contributing to improving the quality and safety of dairy products made in the company of dairy VERITO; with the aim of developing a Manual of Good Manufacturing Practices. To consolidate the development of the manual; previously the current situation in which there is the small business with the help of a checklist based on the requirements of the Rules of Good Manufacturing Practices for processed foods No. 3253 issued by the Constitutional Court in 2002. By assessed the facilities, equipment and utensils, personal, raw materials and inputs, production operations, packaging, labeling and packaging, storage, distribution, transportation and marketing and quality assurance and control: which the following aspects were evaluated.